Inversión Extranjera Directa y Desempeño Del Sector Agrícola En El Ecuador, Periodo 1970-2020. - Agualongo Morocho, Alex Andres (2023)
The research project called foreign direct investment and performance of the agricultural sector in Ecuador, Period 1970-2020; Its objective is to analyze the relationship between the study variables and explain the influence of foreign direct investment and its performance in the agricultural sector of Ecuador. To do this, a relationship is established between the gross added value of agriculture as the dependent variable and the independent variables are made up of foreign direct investment, inflation, trade liberalization and gross fixed capital formation. Due to the proposed research approach, it was carried out through the application of an econometric model, using an error correction model (VEC) and cointegration was also used, in order to explain the relationship of the variables in the short term. and long erm, obtaining as a result the existence of a negative relationship in the short term of that of direct foreign investment and the gross value added of agriculture, however, a positive relationship was evidenced in the long term between direct foreign investment and the agricultural sector. It is concluded that the study variables presented a positive relationship and allows us to explain that direct foreign investment affects unemployment in the agricultural sector in the long-term period.